Gaelic Song in Eastem Canada: Twentieth-Century Reflections - Bennett, Margaret (Ethnologies, 1992)
More than two centuries have passed since Canada became home to boatloads of Gaelic-speaking immigrants from the Highlands and Islands of Scotland. Though materially impoverished, they brought with them a wealth of oral tradition and a lifestyle characterised by the «taigh ceilidh» [visiting house] which promoted the continuation of their songs and stories. In the closing decade of the twentieth century thousands of Gaelic songs remain as a testimony to generations of tradition, reflecting the ancient bardic pattern of the Gaels, recording their joys, sorrows, hopes, glories, and their unwritten history. This paper looks at the range of material which survives in the Maritimes, Newfoundland and Quebec, and comments upon the significance of it to Canadians today.